That one should disdain hardships : the teachings of a Roman Stoic - Musonius Rufus, C. (Caius), approximately 30- (Yale University Press, 2020)
Perennial wisdom from one of history's most important Stoic teachers The Stoic philosopher Musonius Rufus was one of the most influential teachers of his era, imperial Rome, and his message still resonates with startling clarity today. Alongside Stoics like Seneca, Epictetus, and Marcus Aurelius, he emphasized ethics in action, displayed in all aspects of life. Merely learning philosophical doctrine and listening to lectures, they believed, will not do one any good unless one manages to interiorize the teachings and apply them to daily life. In Musonius Rufus's words, "Philosophy is nothing else than to search out by reason what is right and proper and by deeds to put it into practice." At a time of renewed interest in Stoicism, this collection of Musonius Rufus's lectures and sayings, beautifully translated by Cora E. Lutz and introduced by Gretchen Reydams-Schils, offers readers access to the thought of one of history's most influential and remarkable Stoic thinkers.